Peran Gereja dalam Merespons Konflik Sosial yang Dialami Masyarakat Adat di Kabupaten Yahukimo Papua Pegunungan - Hulu Yerdin Kobak (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
Social conflicts experienced by indigenous peoples in Yahukimo Regency, Papua Pegunungan, reveal the vulnerability of civilians due to violence, displacement, and weak protection of basic rights in situations of prolonged conflict. These conditions indicate a gap between conflict management policies and the real needs of indigenous peoples for justice, peace, and social recovery. This study aims to analyze the role of the church in responding to social conflicts experienced by indigenous peoples in Yahukimo Regency. This study was conducted using qualitative methods through a descriptive-analytical approach based on literature studies and analysis of the socio-religious context of Papua. This study confirms that the church has a strategic role as an agent of peace and a prophetic voice in defending the dignity and rights of indigenous peoples amid social conflict. The results of the study show that the church's involvement in pastoral counseling, humanitarian advocacy, and peace awareness building contributes to strengthening the social resilience of indigenous peoples. The study concludes that the role of the church needs to be directed in a more contextual and sustainable manner in order to promote fair and dignified conflict resolution. The recommendations of this study emphasize the importance of strengthening the role of the church in peace dialogue and cross-stakeholder cooperation for the social recovery of indigenous peoples in Yahukimo.